PERAN FOOD AND AGRICULTURE ORGANIZATION (FAO) DALAM MENANGANI KRISIS PANGAN DI AFGHANISTAN PADA TAHUN 2018- 2023 - Audina, Fadila; Saeri, Mohammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This research discusses the role of the Food and Agriculture Organization (FAO) in dealing with the food crisis in Afghanistan in 2018-2023. The food crisis in Afghanistan, which reached its peak in 2018, requires the role of international organizations such as FAO. This research aims to analyze FAO's actions in addressing the crisis. FAO runs programs that have had significant results in reducing food insecurity levels, including rebuilding water management systems for agricultural success, accessing roads, strengthening river banks, and implementing river flow management activities. FAO also collaborates with various parties and provides technical and financial assistance to Afghanistan. FAO supports the Afghan government in setting zero hunger as a development priority and enhancing zero hunger policy programs through capacity building, advocacy, public awareness, and the establishment of food security and nutrition committees. The results of this paper indicate that FAO plays an important role in helping to deal with the food crisis in Afghanistan by providing emergency and food security assistance, rehabilitating agricultural infrastructure through the IRDP program, servicing the food and nutrition sector. This has resulted in a significant decrease in the number of Afghans experiencing acute food insecurity, from 23 million in 2022 to 14.2 million in 2024. Keywords: Food and Agriculture Organization (FAO), Food Crisis